Pembelajaran Berdiferensiasi Perspektif Kurikulum Merdeka - Astuti, Mardiah; Agustin, Linda; Alhusaini, M. Yunus; Anggraini, Tria; Adellia, Serhli (Indo-MathEdu Intellectuals Journal, 2025)
This study employs a qualitative method with a literature review approach. Literature review research is a method aimed at analyzing and synthesizing information available from various literature sources. In differentiated learning, the teacher's role is crucial in determining the success of the learning process. Teachers must be creative in selecting models, techniques, and strategies that encourage active student participation, thereby improving the quality of classroom learning. The Merdeka Belajar (Freedom to Learn) program highlights the importance of adapting instructions to diverse needs, skills, interests, and learning preferences of students. This idea aligns with the philosophy of the Merdeka Curriculum, which grants educators the autonomy to create learning experiences that are more adaptable and contextually relevant. In practice, differentiated learning requires offering a variety of approaches, resources, and evaluation techniques based on the unique needs and capabilities of each student. While differentiated learning has the potential to enhance students' enthusiasm and engagement, its implementation faces challenges, including limited resources, inadequate teacher understanding, and inconsistent institutional support. Therefore, to facilitate the application of more individualized and flexible teaching methods, it is essential to improve teacher preparation programs and provide adequate facilities